Antecedents to Thai Consumer Insurance Policy Purchase Intention: A Structural Equation Model Analysis - Kumpee Thamtarana; Puris Sornsaruht (My University, 2024)
This study delves into the factors influencing consumer purchase intention of Thai insurance company policies, focusing on service quality, corporate image, perceived value, and insurance technology. Employing a quantitative approach and multi-stage random sampling, the study selected 440 consumers from 10 Thai insurance agencies in January 2022, using a Google Form link distributed via social media for data collection. The structural equation model path analysis was conducted using LInear Structural RELations (LISREL) 9.1, complemented by descriptive statistics analysis in Statistical Package for the Social Sciences (SPSS) for Windows Version 21. Expert input informed adjustments to questionnaire items, and a pilot test with 35 participants ensured item reliability. The results reveal that insurance technology (0.68), corporate image (0.54), perceived value (0.53), and service quality (0.34) were all influential factors affecting purchase intention, collectively explaining 76% of the variance ( R 2 ). Seven of the nine hypotheses tested found support, with the corporate image-perceived value relationship proving the strongest, followed by a moderately strong association between perceived value and insurance technology. Among the 25 observed variables, the quality of services and data standards provided by service quality stood out, with consumers valuing clear, concise, and convenient services as pivotal for agency satisfaction. This research contributes to the existing literature by offering post-COVID-19 insights into consumer insurance purchase intentions in Asia. It also provides valuable knowledge for policymakers and regulators seeking to enhance their sectors and strengthen national economic competitiveness.
Keywords: Consumer Retail Behavior Studies